INTL ASSN OF FIRE FIGHTERS - WHITEHEAD,AK (Tufts Archival Research Center, 2007)
Letter from the International Association of Firefighters to Jaqueline Jones Smith, the chairperson of the US Consumer Safety Commission regarding a petition submitted to the CSC from the National Association of State Fire Marshalls. Declares that they can no longer support the bill due in part to its divergence from the recommendations of CAL 133 full flame testing in public places. Says that the NASFM petition is counterproductive to the goals of the IASF but that they hope to work with them in the future on building upon the successes the IASF has already achieved.